1996
DOI: 10.1093/oxfordjournals.humrep.a019285
|View full text |Cite
|
Sign up to set email alerts
|

Does the absence or presence of seminal fluid matter in patients undergoing ovulation induction with intrauterine insemination?

Abstract: Sperm preparations for intrauterine insemination (IUI) generally do not include seminal fluid, and it is not known whether the absence of this component affects pregnancy rates. Therefore we evaluated the effect of high intravaginal seminal fluid deposition on clinical pregnancy rates in patients undergoing ovulation induction and IUI therapy. A prospective, randomized, double-blind study was designed for an infertile population in a university-based infertility practice. Patients were randomized to receive hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Embryo implantation rates were not different in a third study in couple who had coitus at least once 12 hr after embryo transfer 51 . A study in which seminal fluid was placed intravaginally at the time of intrauterine insemination (IUI) with spermatozoa washed out of semen revealed no difference in pregnancy rate when compared with a saline control 52 . Unfortunately, all of these studies were of small size and did not define their clinical populations well.…”
Section: Why Don’t Women Develop An Immunity To Sperm?mentioning
confidence: 99%
“…Embryo implantation rates were not different in a third study in couple who had coitus at least once 12 hr after embryo transfer 51 . A study in which seminal fluid was placed intravaginally at the time of intrauterine insemination (IUI) with spermatozoa washed out of semen revealed no difference in pregnancy rate when compared with a saline control 52 . Unfortunately, all of these studies were of small size and did not define their clinical populations well.…”
Section: Why Don’t Women Develop An Immunity To Sperm?mentioning
confidence: 99%
“…Qasim found that application of SP in vagina during intrauterine insemination does not improve the pregnancy rate [15]. Fishel found no difference in the pregnancy and miscarriage rates between 2 groups with or without SP (32 % versus 33 % and 21 % versus 17 %) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the role of SP in implantation with controversial results, some reporting benefits [1,19,21], whereas others showing no effect [6,15].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of clinical pregnancy rates between two groups showed no significant difference. Further in non-participants with unregulated intercourse, the pregnancy rates were not significantly different (25). Coulam and Stern suggested that higher implantation rates were obtained in a group of women experiencing infertility and/or recurrent spontaneous abortion who received vaginal capsules of seminal plasma versus placebo, however this difference was not significant (26).…”
Section: Clinical Studiesmentioning
confidence: 99%